2016
DOI: 10.1128/aem.03056-15
|View full text |Cite
|
Sign up to set email alerts
|

Multiple Posttranslational Modifications of Leptospira biflexa Proteins as Revealed by Proteomic Analysis

Abstract: cThe saprophyte Leptospira biflexa is an excellent model for studying the physiology of the medically important Leptospira genus, the pathogenic members of which are more recalcitrant to genetic manipulation and have significantly slower in vitro growth. However, relatively little is known regarding the proteome of L. biflexa, limiting its utility as a model for some studies. Therefore, we have generated a proteomic map of both soluble and membrane-associated proteins of L. biflexa during exponential growth an… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
21
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 11 publications
(22 citation statements)
references
References 58 publications
1
21
0
Order By: Relevance
“…More recently, it was shown that protein expression, in response to changing environmental conditions, can be modified further by specific post-translational modifications (PTM; Eshghi et al, 2012 ). Indeed, both saprophytic and pathogenic leptospires have comprehensive bio-systems to modify proteins (Cao et al, 2010 ; Schmidt et al, 2011 ; Stewart et al, 2016 ). Recently, 32 phosphorylated, 46 acetylated, and 155 methylated proteins were identified that not only confirmed multiple modifications in prokaryotes, but also suggests that L. interrogans shares significant similarities with protein modification systems in eukaryotes (Cao et al, 2010 ).…”
Section: Introductionmentioning
confidence: 99%
“…More recently, it was shown that protein expression, in response to changing environmental conditions, can be modified further by specific post-translational modifications (PTM; Eshghi et al, 2012 ). Indeed, both saprophytic and pathogenic leptospires have comprehensive bio-systems to modify proteins (Cao et al, 2010 ; Schmidt et al, 2011 ; Stewart et al, 2016 ). Recently, 32 phosphorylated, 46 acetylated, and 155 methylated proteins were identified that not only confirmed multiple modifications in prokaryotes, but also suggests that L. interrogans shares significant similarities with protein modification systems in eukaryotes (Cao et al, 2010 ).…”
Section: Introductionmentioning
confidence: 99%
“…We termed the bactofilins of L. biflexa LbbA‐E, for Leptospira biflexa bactofilins A‐E, ranked by increasing number of amino acids (Table ). LbbD was the only bactofilin identified from a previous proteomic mapping experiment (Stewart et al ., ) and we selected this protein for further characterization of its contribution to L. biflexa morphology and physiology.…”
Section: Resultsmentioning
confidence: 99%
“…Furthermore, qRT‐PCR analysis of wild type and ΔLBBD strains for flaB transcript normalized to putative outer membrane protein B0SQ62 (Uniprot) demonstrated similar levels between strains (data not shown). This outer membrane protein was previously identified as an abundant membrane‐associated protein with Uniprot accession B0SGK2 (Stewart et al ., ). Finally, mutant cell morphology during translation in viscous media was similar to that of wild type (Supporting Information Figs S2 and S3).…”
Section: Discussionmentioning
confidence: 97%
See 2 more Smart Citations